EFFECT OF GENOTYPES AND NITROGEN LEVELS ON PRODUCTION POTENTIAL OF MAIZE (ZEA MAYS L.) UNDER INDO-GANGATIC PLAIN ZONE OF WESTERN U.P. - SINGH, PRADEEP; N. S. RANA,; U. N. SHUKLA,; RAKESH KUMAR, SMITA SINGH; KUMAR, KAUSHAL (The Bioscan, 2012)
Among genotypes, Dekalb 900 M Gold had significantly higher yield attributes viz. cobs/plant, cob length (cm), grains/row, grains/cob, 1000 grain weight, ten cobs weight, grain weight/ten cobs, shelling percentage, grain yield (6340 kg/ha), stover yield (8550 kg/ha), benefit: cost ratio (2.0), crop profitability (329.47 /ha/day) and crop productivity (62.35 kg/ha/day). Crop fertilized with 160 kg N/ha registered significantly higher yield attributes viz. cob length, cob girth, grain rows/cob, grains/row, grains/cob, 1000 grain weight, ten cobs weight, grain weight/ten cobs, shelling percentage, grain yield (6240 kg/ ha) and stover yield over 40 kg N/ha, but it was at par with 120 N kg/ha. However, the highest benefit: cost ratio (2.0), crop profitability (322.42/ha/day) and crop productivity (61.76 kg/ha/day) with the application of 120 kg N/ha closely followed by 160 kg N/ha. Harvest index, grain rows/cobs and cobs girth did not influenced by any of the genotypes and N levels.